EDUKASI STRUKTUR ANATOMI DAN TAHAPAN ERUPSI GIGI PADA MASYARAKAT KALIGAWE SEMARANG: PENDEKATAN PENYULUHAN INTERAKTIF - Recita Indraswary; Arina Shafia; Alex Amrullah (LPPM Universitas Abdurrab, 2025)
Public awareness of the importance of maintaining oral and dental health remains a challenge in Kaligawe, Semarang City. Limited understanding of dental anatomy and tooth eruption stages often leads to delayed detection of dental problems, particularly in children. To address this issue, an educational program was conducted with the aim of improving community knowledge through an approach that is easy to understand and encourages active participation. The educational session was delivered to 85 participants, with an intervention duration of 30 minutes. The program began with a brief survey to identify community needs. Educational materials were prepared contextually to align with local social and cultural conditions. The session utilized visual media, three-dimensional models, and hands-on demonstrations, accompanied by group discussions that allowed participants to ask questions and share their experiences. Community members were actively involved, including in the formation of small groups responsible for continuing the education in their respective neighborhoods. The results showed a significant increase in understanding. The average pre-test score of 55 percent rose to 85 percent in the post-test. In addition to the improved scores, the participants’ enthusiasm and engagement also reflected the success of the program. Several challenges, such as time constraints and diverse educational backgrounds, were managed through a flexible and approachable delivery method. This initiative demonstrated that educational programs delivered in a simple and community-responsive manner can lead to positive behavioral changes. It is hoped that the activity can be sustained, expanded in its reach, and serve as a model for other areas facing similar issues in oral and dental health, particularly in communities with limited access to preventive healthcare services.